Pengaruh Keputusan Pembiayaan Utang dan Pembiayaan Ekuitas Terhadap Green Accounting - Saragih, Afni Eliana (Universitas Hamzanwadi, 2024)
Environmental management has become increasingly urgent and a global concern, leading governments to mandate all companies implement environmentally friendly practices known as green accounting. The study aims to analyze the impact of debt financing and equity financing decisions on green accounting in developing countries. Secondary data was collected from manufacturing firms in the basic industry and chemical sectors listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. Panel data regression analysis was employed, preceded by a test to determine the most suitable model among the Fixed Effect Model (FEM), Common Effect Model (CEM), or Random Effect Model (REM). The results indicate that debt financing inversly on green accounting while equity financing have a positive significant effect on green accounting. Decisions regarding debt financing and equity financing affect the level of a company's involvement in green accounting practices.